How friends’ involvement in crime affects the risk of offending and victimization - Rokven, Josja J. (European journal of criminology, 2017)
Restorative justice (RJ) promotes a constructive dialogue between the victim of a crime and the offender. Restorative practices have been credited for allowing victims to move on from victimization. This paper goes beyond victim appreciation of RJ and addresses what motivates victims to agree to communicate with their offender. Victim-participants were interviewed at the start of a restorative intervention and again after its conclusion, with the aim of identifying reasons for participation and exploring whether these evolve as a restorative procedure progresses. Discourses reveal that victims hoped that interaction with their adult or young offender would advance insight and healing as well as help the offender. Shifts in motivation over time were only subtle and many respondents manifested prosocial intentions (for example to help the offender) early on.